Tissue distribution of endogenous cobalamins and other corrins in the rat, cat and guinea pig - Quadros, Edward V.; Matthews, David M.; Wise, Irene J.; Linnell, John C. (Biochimica et biophysica acta, 1976)
1. 1. Methylcobalamin, adenosylcobalamin, hydroxocobalamin and cyanocobalamin have been estimated by a chromato-bioautographic technique in 16 tissues from healthy rats and in five guinea pig tissues. 2. 2. Plasma and erythrocyte cobalamins have been estimated in rats, cats and guinea pigs and the results compared with those in man. 3. 3. Unidentified corrins were detected in 8 of the 16 rat tissues and in 3 of the 5 guinea pig tissues analysed, but were not present in tissues from specific pathogen-free rats nor in the standard laboratory diet. 4. 4. Adenosylcobalamin was the major corrin in 8 of the 16 rat tissues. In the remainder hydroxocobalamin predominated or was present in equal proportions with adenosylcobalamin. Methylcobalamin was detected in the majority of rat tissues but at levels much lower than those in human tissues. Small amounts of cyanocobalamin were detected also and levels were higher than those of methylcobalamin in 8 of the 16 tissues. 5. 5. In the rat, cat and guinea pig, levels of methylcobalamin and hydroxocobalamin were higher in erythrocytes than in plasma, a pattern almost the complete reverse of that in man.